Interventional ultrasound : a practical guide and atlas - Dietrich, Christoph Frank; Nuernberg, Dieter (Thieme, 2015)
The first comprehensive, multi-specialty text on ultrasound guidance in interventional procedures, this book uses the authors extensive clinical experience to provide a full overview of modern interventional ultrasound. For all practitioners, whether new to the procedures or already using them, Interventional Ultrasound offers expert advice and solutions to commonly encountered questions and problems. Special Features: Provides a complete approach to interventional ultrasound, beginning with essential basics on materials, equipment, setup requirement.